2015
DOI: 10.1080/10934529.2015.1019805
|View full text |Cite
|
Sign up to set email alerts
|

Effect of mercury on porcine ovarian granulosa cellsin vitro

Abstract: The objective of this in vitro study was to examine dose-dependent changes in the secretion activity [progesterone (P4) and insulin-like growth factor-I (IGF-I)] of porcine ovarian granulosa cells after experimental mercury (Hg) administration, including its apoptotic potential so as to ascertain the possible involvement of Hg in steroidogenesis. Ovarian granulosa cells were incubated with mercuric chloride [mercury (II) chloride or HgCl2] at the doses 50-250 μg mL(-1) for 18 h and compared with control group … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 52 publications
2
3
0
Order By: Relevance
“…An increasing trend of apoptosis of granulosa cells was confirmed. Results of this study also confirm a direct effect of mercury on the release of steroid hormone progesterone as well as interference of mercury in the pathways of steroidogenesis and apoptosis [ 161 ]. Other data confirm that mercury administration has a dose-dependent association with the hormonal release by porcine ovarian granulosa cells [ 162 ].…”
Section: Mercury (Hg)supporting
confidence: 73%
“…An increasing trend of apoptosis of granulosa cells was confirmed. Results of this study also confirm a direct effect of mercury on the release of steroid hormone progesterone as well as interference of mercury in the pathways of steroidogenesis and apoptosis [ 161 ]. Other data confirm that mercury administration has a dose-dependent association with the hormonal release by porcine ovarian granulosa cells [ 162 ].…”
Section: Mercury (Hg)supporting
confidence: 73%
“…Moreover, the level of progesterone liberated was inhibited from the ovarian granulosa cells of pigs exposed to mercury. This confirms a direct effect of mercury on the secretory release of progesterone as well as interference of Hg in the pathways of steroidogenesis and apoptosis (Knazicka et al 2013;Roychoudhury et al 2015). In the current work, a highly significant decrease in the levels of serum FSH, LH, estrogen, and progesterone was recorded among HgCl2-treated mother rats and their offspring.…”
Section: Discussionsupporting
confidence: 84%
“…The obtained result goes parallel with the finding of rats to two high doses of HgCl2 (5 and 10 mg/kg b.wt) for 48 hours is implicated in the induction of cellular apoptosis in both testes and kidneys (Massanyi et al 2007). The apoptotic effect of mercury is fundamentally attributed to its direct effect on the release of steroid hormones and interference with the pathways of steroidogenesis resulting in apoptosis (Roychoudhury et al 2015).…”
Section: Heath Et Al Studied the Effects Of Two Doses Ofmentioning
confidence: 99%
“…The involvement of Hg on cellular processes of progesterone secretion has also been studied in mammalian models. On porcine model, previous study showed that HgCl 2 reduced cell viability and inhibited the progesterone synthesis in porcine ovarian granulosa cells (Roychoudhury et al., ).…”
Section: Discussionmentioning
confidence: 96%